2019
DOI: 10.1186/s13063-018-3100-y
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Communities Learning About Second-hand Smoke in Bangladesh (MCLASS II): study protocol for a cluster randomised controlled trial of a community-based smoke-free homes intervention, with or without Indoor Air Quality feedback

Abstract: BackgroundSecond-hand smoke (SHS) is a serious health hazard costing 890,000 lives a year globally. Women and children in many economically developing countries are worst affected as smoke-free laws are only partially implemented and homes remain a major source of SHS exposure. There is limited evidence on interventions designed to reduce SHS exposure in homes, especially in community settings. Following a successful pilot, a community-based approach to promote smoke-free homes in Bangladesh, a country with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…A second approach that has shown initial promise is currently being trialled in Bangladesh to evaluate the effectiveness of a community-based intervention to reduce SHS exposure at home, primarily targeting men via mosques [48]. This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second approach that has shown initial promise is currently being trialled in Bangladesh to evaluate the effectiveness of a community-based intervention to reduce SHS exposure at home, primarily targeting men via mosques [48]. This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50]. If found to be effective in changing smoking behaviour in the home, this approach could be generalizable to other communities with similar male smoking norms where faith-based settings (i.e., churches, mosques, synagogues) play an integral part in their lives [48].…”
Section: Discussionmentioning
confidence: 99%
“…The recent availability of low-cost particle counting monitors has also made it possible to assess concentrations of PM more widely, both indoors and outdoors. As part of the MCLASS II (Muslim Communities Learning About Second-hand Smoke in Bangladesh) study, 15 a trial of a novel smoke-free homes intervention, 24 h measurements of indoor PM were made in 1,801 homes around Dhaka, Bangladesh, using one such monitor, the Dylos DC1700 particle counter (Dylos Corp, Riverside, CA, USA). These data included 779 homes where smoking was not reported to take place.…”
mentioning
confidence: 99%
“…Finally, one study each was included from other countries as mentioned in Table 2. However, no study from other developing countries such as India, Nepal and Bangladesh that are greatly affected by IAP due to inadequate ventilation arrangements were included [13,42,48,53,83,100]. As the majority of the population in these countries use biomass fuels for cooking and heating purpose, the researchers in these locations need to show an active participation in the development of some potential IAQ monitoring and prediction systems that can provide more accurate results based on specific geographic conditions and pollutant concentrations [61,85,138].…”
Section: Resultsmentioning
confidence: 99%